2019
DOI: 10.5194/angeo-2019-19
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Response of low to mid latitude ionosphere to the Geomagnetic storm of September 2017

Abstract: Abstract. We study the impact of geomagnetic storm of September 6–9, 2017 on the low-to-mid latitude ionosphere. The prominent feature of this solar event is the sequential occurrence of the two Dst minima of maximum negative values −148 nT and −122 nT on September 8 at 2 UT and 15 UT, respectively. The study is based on analyzing the data from GPS stations and the magnetometer observatories located at different longitudinal sectors such as Asia, Africa and America. The GPS data is used to derive the global, r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…Thus, according to the results obtained in this study, the disturbances over Turkey' ionosphere is negative in the beginning and main phases of the geomagnetic storm and is positive in the return phase of the geomagnetic storm. These results are consistent with the literature (Imtiaz et al, 2019). However, this research can be expanded by using more stations from the TUSAGA-Active network in more storm periods to obtain clearer information.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, according to the results obtained in this study, the disturbances over Turkey' ionosphere is negative in the beginning and main phases of the geomagnetic storm and is positive in the return phase of the geomagnetic storm. These results are consistent with the literature (Imtiaz et al, 2019). However, this research can be expanded by using more stations from the TUSAGA-Active network in more storm periods to obtain clearer information.…”
Section: Discussionsupporting
confidence: 92%
“…The strength of a geomagnetic storm is characterized by a minimum Dst (Disturbancestorm time) index (Gonzalez et al, 1994). Based on this parameter, geomagnetic storms can be classified as: Small Storm (Dst ≤ −30nT), moderate storms (Dst ≤ −50nT), dense storm (Dst ≤ − 100nT) and large storm (Dst ≤ -200nT) (Imtiaz et al, 2019;Loewe and Prölss, 1997;Tsurutani et al, 1992). Geomagnetic storms cause disturbances in the Earth's magnetic field, resulting in various inhomogeneous processes in the Earth's ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in the amplitude of westward winds with magnetic activity is also reported by Fejer et al (2002). Nadia et al (2019) reported the same behavior of the increase in VTEC during the storm period, and they are found in the African region; the largest increase in the VTEC is observed for the equatorial latitude station NKLG in Africa (geographic coordinates: 0.35°N, 9.67°E) during the storm. On day after the beginning of storm main phase onset, a negative effect is observed in the northern midlatitude station, whereas for earlier results on low and equatorial storms, Walker (1973) reported for Hong Figure 11.…”
Section: Superposed Epoch Analysissupporting
confidence: 84%
“…Over Europe, results of maximum electron concentration of the ionospheric F2 layer (NmF2) increase and decrease on 7 and 8 September, respectively, for Ebre (40.8°N, 0.5°E) have been reported (Cander, 2019). Thermospheric O/N 2 ratio results from the Global Ultraviolet Imager (GUVI) onboard TIMED satellite published in (Imtiaz et al, 2020) show enhanced and depleted values over the analyzed locations in the Southern and Northern Hemispheres, respectively, on 8 September 2017. Temporal evolution of TEC and electron density dynamics indicate that the Southern Hemisphere midlatitude region was under the influence of competing/opposing processes arising from the EIA expansion and neutral composition changes as a result of heated lower parts of the thermosphere in auroral and/or high latitudes (Buonsanto, 1999; Yizengaw et al, 2005).…”
Section: Resultsmentioning
confidence: 99%